Implementation of an Individualized Learning Program for Children with Autistic Spectrum Disorders at a Therapy Centre for Children with Special Needs - Reza, Fatih Ibnu (Universitas Pendidikan Indonesia (UPI), 2024)
In the world of health, education, and children, we often hear the term autistic child as a designation for children who are seen as different in their communication and social interaction abilities. The aim of the research is to determine the process of implementing an individual learning program for children with non-verbal autism spectrum disorders at the Therapy Centre for Children with Special Needs. Using a qualitative approach with a case study design, this research analyses every stage from the process of preparing, implementing, to evaluating children's learning programs. The results of the research show that the lack of interventionist consistency in providing learning materials to children has an impact on the process, implementation, and evaluation of learning to children. Learning program planning aims to design student experiences to achieve learning goals. The implementation of the learning program is taken from the results of the Beginning Curriculum Guide assessment which is designed into several learning aspects consisting of recognizing objects and body parts, toilet training, using yes and no signals, and carrying out activities slowly. From the evaluation results, it is stated that interventionist consistency in providing children's learning materials is very important and needed.